Рolymorphism study of cytochrome P450 gene in patients with glaucoma (Eurasian Journal of Ecology, 2016)
Glaucoma – one of the widespread eye diseases bringing people to violation of visual functions, and also to a blindness. One of factors of development of glaucoma is heredity. Diagnostics at early stages is one of key factors of preservation of sight at the patient with primary open-angle glaucoma (POAG). 63 patients with POAG are investigated and the group of control made 25 people. Polymorphism gene cytochrome P450 associated with development of a hereditary form of glaucoma is revealed. Frequency of occurrence made 64% in Kazakhstan.
Keywords: glaucoma; genetics; mutation; PCR; RFLP analysis